A first Triassic insect from Antarctica (Eisenhower Range, northern Victoria Land) - Lara, Maria Belén (2024)
We report here an isolated insect forewing from Triassic deposits of the Eisenhower Range, northern Victoria Land, Antarctica. Based on the reduced venation (e.g. well-developed pterostigma, Rs dichotomously branched, Rs and M vein with five branches each), we tentatively identify the specimen as belonging to Permochoristidae (Mecoptera). However, due to incomplete preservation of the forewing, we prefer a determination under open nomenclature until more material of this taxon is available. The new specimen represents the first insect described from the Triassic of Antarctica and the first fossil record of Mecoptera in the continent, supporting the worldwide distribution and a greater diversity of the family during Triassic times.